Air-side heat transfer characteristics of ambient air vaporizers with various geometric parameters under cryogenic frosting conditions. (March 2022) - Kwon, Junho; Yun, Sungho; Lee, Sewon; Cho, Wonhee; Kim, Yongchan
Highlights: Heat transfer performances of AAVs are measured under cryogenic frost conditions. Frost growth characteristics of AAVs are analyzed with operating variables. The performance of AAVs is compared with geometric design parameters. An empirical correlation for the Nusselt number (Nu) is developed for AAVs. Abstract: Ambient air vaporizers (AAVs), which utilize air as a heat source, have been widely used for natural gas regasification. Under cryogenic frosting conditions, the heat transfer performance of AAVs is gradually reduced owing to frost growth on the fin surface. In this study, the heat transfer characteristics of AAVs were measured and analyzed by varying the geometric design parameters and operating variables under cryogenic frosting conditions. The air velocity, relative humidity, and temperature were selected as the operating variables, and the fin height, fin tip distance, and fin pitch were considered as design parameters. The frost growth was accelerated with increasing air velocity, humidity, and temperature under cryogenic frost conditions. Furthermore, as the fin height, fin tip distance, and fin pitch increased, the heat transfer reduction and pressure drop with respect to time decreased owing to the decrease in the blockage ratio. In addition, an empirical correlation for the Nusselt number in AAVs was developed as a function of the operating variables and geometric parameters based on the measured data. The present results can be used as practical design guidelines for AAVs under actual operating conditions.